Metal-organic double layer to stabilize selective multi-carbon electrosynthesis - Jian Cheng; Ling Chen; Yanzhi Zhang; Min Wang; Zhangyi Zheng; Lin Jiang; Zhao Deng; Zhihe Wei; Mutian Ma; Likun Xiong; Wei Hua; Daqi Song; et al. (Nature Communications)
Abstract Stable operation of the gas diffusion electrodes is key for industrial-scale electrochemical CO2 reduction (eCO2R). To enhance the electrolytic stability, we shield the Cu-coated gas diffusion electrode with a polycationic sheath via electrospinning and propose a Metal-Organic Double Layer (MODL) scheme to depict the triphasic interface. The as-fabricated electrode exhibits a high multi-carbon Faradaic efficiency of 91.2 ± 3.8%, along with operational stability for over 300 h at 300 mA cm−2 in an alkaline flow cell. In a membrane electrode assembly with pure water as the anolyte, it further achieves an ethylene Faradaic efficiency over 50% at 200 mA cm−2. Mechanistic investigations unveil that replacing hydrated cationic counter ions in the conventional double layer with hydrogen bond-woven polycationic groups in the MODL allows simultaneously tailoring the local electric field and interfacial water structure. This study introduces a molecular-level redesign of the electric double layer in eCO2R systems, achieving precisely tunable electrostatic characteristics and tailored chemical microenvironments while leveraging sustainable electrolysis systems to enable highly efficient and stable multi-carbon production.